2022
DOI: 10.1093/rpd/ncac187
|View full text |Cite
|
Sign up to set email alerts
|

Substantial External Dose Rate Variability Observed in a Cohort of Lu-177 Patients Independent of Bmi and Sex

Abstract: External dose rates were measured 1 m away from 230 Lu-177 patients to characterise the variability in normalised dose rates as a function of administered activity, body mass index (BMI) and sex. The largest dose rate observed was 0.07 mSv/h associated with an administered activity of 7.2 GBq. Substantial variability was found in the distribution of the normalised dose rate associated that had an average of 0.0037 mSv/h per GBq and a 95% confidence interval of 0.0024–0.0058 mSv/h per GBq. Based on this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It is worth noting that the phantom used in the study is not representative for all patients, especially for over-weighted or under-weighted patients. A study has demonstrated a significant negative correlation between extracorporeal dose rate and patient Body Mass Index (Bellamy et al 2022). Therefore, further studies on the introducing errors in the assessment and simulations are needed, and the results could be verified by patient measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the phantom used in the study is not representative for all patients, especially for over-weighted or under-weighted patients. A study has demonstrated a significant negative correlation between extracorporeal dose rate and patient Body Mass Index (Bellamy et al 2022). Therefore, further studies on the introducing errors in the assessment and simulations are needed, and the results could be verified by patient measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In our data collection, most patients were of normal weight or overweight. There are studies, which have observed that medications (mTOR-Inhibitors or PRRT) are not ideally calculated according to BMI [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…However, first the calculation is not straightforward, unless the exposure rate constant is used and thus the point source approximation. Second, whole-body or organ activity are highly variable: illustrative examples can be found in Kurth et al (2018), Mair et al (2018), Levart et al (2019) and Bellamy et al (2022) for lutetium therapy and in Berg et al (1996), Areberg et al (2005) and Hänscheid et al (2006) for radio-iodine therapy. As such, measurements of the patient dose rate merely serve as a normalisation of the dose rate pattern given by biokinetic models.…”
Section: Introductionmentioning
confidence: 99%